2021
DOI: 10.1073/pnas.2026309118
|View full text |Cite
|
Sign up to set email alerts
|

A genomic region associated with protection against severe COVID-19 is inherited from Neandertals

Abstract: It was recently shown that the major genetic risk factor associated with becoming severely ill with COVID-19 when infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is inherited from Neandertals. New, larger genetic association studies now allow additional genetic risk factors to be discovered. Using data from the Genetics of Mortality in Critical Care (GenOMICC) consortium, we show that a haplotype at a region on chromosome 12 associated with requiring intensive care when infected with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
149
3
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(159 citation statements)
references
References 50 publications
2
149
3
5
Order By: Relevance
“…In a paper published in Nature , Pairo-Castineira et al (2021) identified a significant genetic variant rs10735079 associated with critical illness of COVID-19 in the gene cluster encodes OAS1 , OAS2 , and OAS3 . Interestingly, recent work on archaic human (Neandertal) DNA has identified an additional haplotype in the region of Chromosome 12 containing OAS1 , OAS2 , and OAS3 that protects against severe COVID-19 ( Zeberg and Paabo, 2020 ). Klaassen et al (2020) identified six genetic variants in innate immunity-related genes, including OAS1 (p.Arg130His), which might have predictive value for COVID-19 infection.…”
Section: Resultsmentioning
confidence: 99%
“…In a paper published in Nature , Pairo-Castineira et al (2021) identified a significant genetic variant rs10735079 associated with critical illness of COVID-19 in the gene cluster encodes OAS1 , OAS2 , and OAS3 . Interestingly, recent work on archaic human (Neandertal) DNA has identified an additional haplotype in the region of Chromosome 12 containing OAS1 , OAS2 , and OAS3 that protects against severe COVID-19 ( Zeberg and Paabo, 2020 ). Klaassen et al (2020) identified six genetic variants in innate immunity-related genes, including OAS1 (p.Arg130His), which might have predictive value for COVID-19 infection.…”
Section: Resultsmentioning
confidence: 99%
“…Zeberg and Pääbo have recently reported that the risk of developing clinically more severe COVID-19 is linked to chromosome 3 genetic variations, whereas the risk of developing clinically less severe COVID-19 is linked to chromosome 12 genetic variations. 5,29 Moreover, these risk-altering haplotypes are of Neanderthal origin, and are more prevalent in European populations, compared to populations where COVID-19 death rates are relatively lower (i.e. sub-Saharan Africa, China).…”
Section: Discussionmentioning
confidence: 99%
“…2 Moreover, several human genomic variants have been linked to variations in COVID-19 outcomes. 3-5 On the other hand, COVID-19 traits associated with a positive disease prognosis have received less attention from investigators. One such trait may be headache.…”
Section: Introductionmentioning
confidence: 99%
“…Both OAS genes had reported associations with Urbani infections in human lung cell cultures [32]. Further, associations between the OAS pathway and MERS-CoV and SARS-CoV2 infections have been reported [69] and single nucleotide polymorphisms in OAS genes were found to be involved in the protective effects of Neandertal haplotypes against SARS-CoV2 [70,71]. IFIT3 was one of four IFN-induced proteins with tetratricopeptide repeats whose expression was greatly enhanced by viral infection, IFN treatment, and pathogen-associated molecular patterns [72].…”
Section: Discussionmentioning
confidence: 99%